Tinjauan Hukum terhadap Persekongkolan Tender dalam Pengadaan Barang dan Jasa Pemerintah - M. Kholidul Azhar; Ansori Ansori; Nivarica Aurel Nur Syahputri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Bid rigging, an illegal practice that undermines the principles of fair business competition, is widespread in government procurement of goods and services. The actions of business actors who deliberately control tender winners not only harm the state, but also deprive consumers of their right to obtain quality products and services at competitive prices. This research in-depth analyzes the practice of bid rigging in the perspective of Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, especially Article 22. Using a statutory approach, this research reveals the impact, forms and legal sanctions on the practice. bid rigging in the procurement of government goods and services. It is hoped that the results of this research can provide effective policy recommendations to prevent and take firm action against the practice of bid rigging, so as to create a healthy and fair business competition climate.